Examining Factors Associated with Attrition, Strategies for Retention Among Undergraduate Nursing Students, and Identified Research Gaps: A Scoping Review. - Sheikoleslami, Rohangez Lida; Princeton, Daisy Michelle; Mihaila Hansen, Linda Iren; Kisa, Sezer; Goyal, Alka Rani (Nursing Reports, 2025)
Background/Objectives: High-quality healthcare delivery relies on a on a sustainable nursing workforce. However, rising attrition rates and declining enrollment in nursing programs pose a significant challenge. A comprehensive synthesis of these factors for student attrition alongside effective retention strategies is needed to guide interventions. The aim of this scoping review is to map and synthesize existing evidence on the factors contributing to attrition among bachelor's nursing students and to identify strategies that have been implemented or proposed to improve student retention in undergraduate nursing programs. Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) Checklist and Joanna Briggs Institute (JBI) guidelines, a systematic search was conducted in the following databases: MEDLINE/PubMed, Embase, Web of Science, PsycInfo, CINAHL, and Ovid. This review included peer-reviewed, English-language empirical studies (2010–December 2024) on attrition, dropout, or retention among bachelor-level nursing students, excluding non-nursing, non-bachelor programs, and unpublished studies or studies without primary data. A structured content analysis approach was used to synthesize findings from both qualitative and quantitative studies. Results: After screening titles, abstracts, and full texts, 19 articles were found eligible for inclusion. Analyses of the included studies revealed four key themes contributing to nursing student attrition: academic factors, institutional and social support, personal factors, and economic challenges. Retention strategies were categorized into two overarching themes: academic and non-academic approaches. Conclusions: Bachelor's nursing programs should adopt retention strategies that enhance institutional and social support to reduce attrition. Strengthening supportive environments alongside curricular reform is key to building a resilient nursing workforce and ensuring quality care.